How Immunotherapy Modified the Therapeutic Scenario of Endometrial Cancer: A Systematic Review - Maiorano, Brigida Anna; Maiorano, Mauro Francesco Pio; Cormio, Gennaro; Maglione, Annamaria; Lorusso, Domenica; Maiello, Evaristo (Frontiers in Oncology, 2022)
Background Endometrial cancer (EC) represents the sixth most common female tumor. In the advanced setting, the prognosis is dismal with limited treatment options. Platinum-based chemotherapy represents the actual standard of care in first-line chemotherapy, but no standard second-line chemotherapy is approved, with less than 1/4 of patients responding to second-line chemotherapy. In the last 10 years, immune checkpoint inhibitors (ICIs) have changed the treatment landscape of many solid tumors. Methods The review was conducted according to the PRISMA guidelines. We searched EMBASE, MEDLINE, Cochrane Database, and conference abstracts from international societies, up to November 2021. Clinical trials employing ICIs in advanced EC, written in English, were included. Reviews, letters, and commentaries were excluded. The overall response rate (ORR), progression-free survival (PFS), overall survival (OS), and safety (number and grade of treatment-related adverse events [TRAEs]) were evaluated. Results 15 studies, for a total of 1,627 patients, were included: 14 non-randomized phase I/II trials and 1 randomized phase III trial. Anti-PD1 (pembrolizumab, nivolumab, dostarlimab) and anti-PD-L1 agents (avelumab, atezolizumab, durvalumab) were administered as single agents; pembrolizumab and nivolumab were combined with the tyrosine-kinase inhibitors (TKI) lenvatinib and cabozantinib, respectively; and durvalumab was associated with anti-CTLA4 tremelimumab. 4 studies selected only MSI patients. Single agents determined an ORR from 26.7% to 58% among MSI patients, from 3% to 26.7% among MSS patients. DCR ranged from 53.5% to 88.9% in MSI, 31.4% to 35.2% in MSS patients. The combination of TKI and ICIs determined 32% to 63.6% of ORR in all-comers, 32%–36.2% in MSS patients. 54.2% to 76% of patients developed TRAEs. The combination of ICIs and TKI achieved a higher toxicity rate than single agents (≥G3 TRAEs 88.9%). Conclusion ICIs represent an effective option for pretreated advanced EC patients with a tolerable profile. Given the encouraging results in MSI patients, every woman diagnosed with EC should be investigated for MS status. In MSS women, the combination of ICIs and TKI is more effective than monotherapy, notwithstanding safety concerns. PD-L1 cannot predict ICI response, whereas other biomarkers such as MSI and tumor mutational burden seem more accurate. Ongoing randomized trials will further clarify the role of these therapeutic options. Systematic Review Registration PROSPERO, CRD42021293538.